New Larval Host Plant of Nausinoe perspectata (Fabricius, 1775) from Kolkata, West Bengal, India (Lepidoptera: Crambidae) - Das, Srinjoy; Ghosh, Biswatosh (SHILAP Revista de lepidopterología, 2024)
Jasmin acts as a larval host plant and nectar plant for many insects including different Lepidoptera. Nausinoe perspectata (Fabricius, 1775) a particular species in common mostly feeds on leaves of Jasminum sambac (L.) Aiton. Jasminum multiflorum (Burm. f.) Andrews, under family Oleaceae popularly known as winter jasmine, Indian jasmine, and / or star jasmine is hereby reported as a new larval food plant or host plant for this species, Nausinoe perspectata (Fabricius, 1775) for 1st time from India.